Possible Board Detections in Determining Minimum Wages in The North Sumatera Province - Darmawan Yusuf (International Conference of ASEAN Prespective and Policy (ICAP), 2018)
This research discusses several factors that influence minimum wage policy in North Sumatera Province. This research is conducted descriptive analysis of the factors that affect the wage council in determining the minimum wage determination in the province of north sumatera. The results of this study show that based on the formula with the previous pred times multiplied by the national inflation rate plus the growth of national gross domestic and the bargaining position that occurs between elements in the decision-making forum on minimum wage, the Board of Pengupaham is also a very decisive factor. The governor in determining wages calls for a recommendation from the wage council, while the position of the regional councils in determining minimum wage fixing in northern Sumatra is limited by government regulation in calculating the amount of minimum wage increases annually. can not only refer to the government regulation no.78 of 2015 on remuneration because the regulation is only based on the previous predictive formula multiplied by the national inflation rate plus the growth of national gross domestic. Because each city's resources and livelihoods are different and so the price of goods per place is also different. It should be in accordance with the KHL of each province rather than referring to national inflation and the growth of national gross domestic product.